Analysis of SiC and SiC-Cascode MOSFET in the design of power electronics converters for more electric aircrafts - Osmar Felipe Alves Eleodoro; Vitor Fonseca Barbosa; Gustavo B. Lima; Luiz Carlos Gomes Freitas (Institute of Advanced Engineering and Science, 2022)
Wideband gap (WBG) semiconductors have developed rapidly in recent years, enabling greater efficiency and power density in the design of power electronics converters for several areas of application. In this sense, this work analyzes the efficiency and specificities of silicon carbide (SiC) technologies and their cascode topology (SiC-Cascode), operating at high switching frequencies. The analyzes are performed using a Boost converter designed for conversion systems in the more-electric aircraft (MEA) context, where the alternating current (AC) power systems can operate at fixed frequency (115V/400Hz), or at variable frequency (115V/360-800Hz), such as observe in Boeing 787, and the direct current (DC) power system can operate with a DC bus of 400 V and +/-270 V are normally used. To validate the project, computer simulations were performed and a 1.0kW prototype was built in the laboratory. The performance analyses demonstrates that 97.5% of efficiency is achieved at 500 kHz switching frequency.